Forms of Tolerance Among Surakarta City Residents: A Study of The Implementation of The Praise Tradition - Umu Hana Amini (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2024)
Puji-pujian (praise) is the chanting of selawat or dhikr which is usually done during the break between the call to prayer and the ikamah in the mosque/prayer room. This tradition can be called oral literature. The implementation of praise is often found in Indonesia, especially Java. One of them is Surakarta. With the diversity that exists, the implementation of praise in Surakarta apparently reflects tolerance between its citizens. The qualitative research using descriptive qualitative methods examines the implementation of the tradition of praise in Surakarta, especially in Kentingan, Jebres Urban Village, where the population is quite diverse. Data in the researcher’s research were obtained from observations, interviews, and literature study. The results of the research show that there is no conflict or coercion regarding the implementation of praise. If there is a conflict, the parties resolve it amicably until they find a middle ground. This can then be a form of tolerance towards the implementation or absence of the praise tradition.